An electrical switching device controlled by a magnetic field-dependent impact ionization process - Lee, Jinseo; Joo, Sungjung; Kim, Taeyueb; Kim, Ki Hyun; Rhie, Kungwon; Hong, Jinki; Shin, Kyung-Ho (AMER INST PHYSICS, 2010)
An abrupt change of conductance at a threshold magnetic field was observed in a device consisting of a nonmagnetic narrow-gap semiconductor. The conductance varies more than 25 times as the magnetic field increases. The threshold magnetic field can be tuned using a bias voltage from zero to several hundred Gauss. This large magnetoconductance effect is caused by the magnetic field-dependent impact ionization process. A theoretical model is proposed, and calculations based on this model simulate the experimental results closely. This device may be a good candidate for an electrical switching device controlled by a magnetic field. (C) 2010 American Institute of Physics. [doi:10.1063/1.3532105]
Keywords: SILICON; LOGIC